2009
DOI: 10.4055/cios.2009.1.4.194
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Prognosis of Impingement Syndrome in the Shoulder with Using Quantitative SPECT Assessment: A Prospective Study of 73 Patients and 24 Volunteers

Abstract: BackgroundDiagnosing impingement syndrome without rotator cuff tear usually depends on the physical examination and roentgenography, and obtaining objective evidence for this condition is at best difficult. The purpose of this study was to ascertain whether quantitatively assessing this condition with using single photon emission computerized tomography (SPECT) can diagnose impingement syndrome and predict the postoperative results.MethodsBefore executing arthroscopic or open treatment, SPECT was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The full text articles of the remaining 116 studies were examined for eligibility and 97 studies were identified for inclusion in the review. 7,13, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full text articles of the remaining 116 studies were examined for eligibility and 97 studies were identified for inclusion in the review. 7,13, …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, US was found to be a valuable diagnostic tool in several studies for rotator cuff complete or incomplete tears, MRI was indicated to be accurate in determining Hills-Sach lesions or bony lesions, and MRA was found to be superior in accurately diagnosing labral capsular ligamentous complex lesions such as internal subacromial impingement. 7,114 This research can be used as an aid for the development of diagnostic and treatment protocols. It highlights the most current methods used to diagnose SIS and can help clinicians reflect on what truly defines a case of impingement syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dabei handelt es sich vorwiegend um die 99m Technetium-Szintigraphie [21] und quantitative Einzelphotonenemissionscomputertomographie (SPECT [22]), welche sich zumindest im deutschsprachigen Raum jedoch bislang nicht in der Routine durchgesetzt haben.…”
Section: Projektionsradiographie Computertomographie Andere Verfahrenunclassified